Analysis of Macroeconomic Factors and Financial Performance on the Phenomenon of Sharia Bank Market Share Stagnancy - Wibawa, Aditya Setiaji; Mujib, Abdul (International Journal of Economics (IJEC), 2024)
The Sharia banking market share is still stuck at the level of 7% of total national banking assets until the February 2024 period. Several strategic policies have been implemented by both regulators and Sharia banking players, but this has not yet increased the Sharia banking market share. Several other relevant studies inform that internal factors in the form of financial performance and macroeconomic conditions are one of the causes of the stagnant increase in the market share of sharia banking in Indonesia, so it is necessary to re-examine/analyze these factors. Furthermore, this research aims to analyze the influence of macroeconomic conditions as proxied by the inflation rate and BI rate as well as the financial performance of Sharia banks as proxied by the CAR and FDR ratios on the Market Share of Sharia Banks in Indonesia. The sample in this study was a total of sharia commercial banks and sharia business units with data regression analysis using the help of the Eviews version 12 program. The results of this research show that simultaneously the independent variables (inflation, BI rate, CAR and FDR) in this research have a significant influence on Market Share with a significance level of 5%. Overall, the results obtained show that the variables inflation, BI rate, CAR and FDR influence the Sharia banking Market Share with a significance level of 5%. Partially, inflation and FDR have no effect on the market share of sharia banking, but the BI rate and CAR have a significant effect on sharia banking in Indonesia.